Access to resources buffers against effects of current reproduction on future ability to provide care in a burying beetle. Issue 9 (9th September 2022) - Lambert, Georgia A.; Smiseth, Per T.
Abstract: Studies investigating the trade‐off between current and future reproduction often find that increased allocation to current reproduction is associated with a reduction in the number or quality of future offspring. In species that provide parental care, this effect on future offspring may be mediated through a reduced future ability to provide care. Here, we test this idea in the burying beetle Nicrophorus vespilloides, a species in which parents shift the cost of reproduction toward future offspring and provide elaborate parental care. We manipulated brood size to alter the costs females experienced in association with current reproduction and measured the level of parental care during a subsequent breeding attempt. Given that these beetles breed on carcasses of small vertebrates, it is important to consider confounding effects due to benefits associated with resource access during breeding. We, therefore, manipulated access to carrion and measured the level of parental care during a subsequent breeding attempt. We found that females provided the same level of care regardless of previous brood size and resource access, suggesting that neither affected future ability to provide care. This may reflect that parents feed on carrion during breeding, which may buffer against any costs of previous breeding attempts. Our results show that increased allocation to current reproduction is not necessarily associated with a reduction in future ability to provide care. Nevertheless, this may reflect unique aspects of our study system, and we encourage future work on systems where parents do not have access to a rich resource during breeding. Abstract : We investigated whether females of the burying beetle Nicrophorus vespilloides that invested more during a current breeding attempt were less able to provide care during a subsequent breeding attempt. Our results showed that females maintained the level of care they provided regardless of previous reproductive allocation. This may reflect that females feed on carrion during breeding, which may buffer against costs of previous breeding attempts.